Targeting Alcohol Misuse: A Promising Strategy for Reducing Military Sexual Assaults? - Farris, Coreen (Rand Health Q, 2015)
On the 2012 Workplace and Gender Relations Survey on Active Duty Service Members, 23 percent of female and 4 percent of male service members indicated that they had experienced a completed or attempted sexual assault during their military service. In addition, official numbers show no decline in sexual assaults, despite the implementation of sexual assault prevention programs across the U.S. Department of Defense (DoD). Alcohol misuse is also a problem in the military: One-third of active-duty service members reported binge drinking, a rate that compares unfavorably with that of their civilian counterparts. DoD has invested considerable resources in universal sexual assault prevention programs and social media campaigns, but evaluation results are not yet available, and the effectiveness of these programs is unclear. Research on civilian populations—particularly college students, who share some characteristics with junior enlisted personnel—could provide insights for DoD. For example, the research indicates a connection between alcohol and aggression, including sexual aggression. Alcohol can also have a range of effects on the risk of victimization—from a reduced awareness of risk indicators to incapacitation or unconsciousness. An extensive review of the existing research provides some guidance for how DoD can implement and evaluate efforts to reduce alcohol misuse as part of a larger strategy to reduce the incidence of sexual assault among members of the armed forces.